(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Learning media is a tool or means used to support the learning process to be more effective, interesting, and interactive. The use of the right learning media can help students understand the material more easily, increase learning motivation, and create a fun learning atmosphere. The purpose of this study is to develop and produce educational game learning media to improve understanding of concepts in circulatory system material. This research is part of Research and Development (R&D). The form of design in this study is the ADDIE development model, where this development model consists of 5 stages of Analysis, Design, Development, Implementation and Evaluation. Validation sheets and response questionnaires were used to collect data in this study which was then analyzed in a quantitative descriptive manner. The results of the study showed that the average validity percentage of material experts was 92.08% and media experts were on average 94.44% with very valid criteria. The average student response questionnaire is 82.41% and the average teacher response questionnaire is 93.75% with very practical criteria. The average N-gain of 0.70% is effective. Thus, educational games for understanding concepts are very valid, practical, and effective to be used as a learning medium in the classroom